Forest fragmentation in the Argentine Chaco: recruitment and population patterns of dominant tree species - Torrella, Sebastián Andrés (2015)
The forest in the Central Argentine Chacohas been dramatically fragmented and persists only asisolated patches in an agricultural matrix. In this study,we evaluated the effects of fragmentation on totaldensity, recruitment, and size-class structure of itsdominant tree species, a key issue, although littleexplored, for forest conservation in the region. Weparticularly analyzed the effects of fragment size andforest cover at landscape level on seven of the mostimportant tree species of the forest. Our results suggestthat forest cover at landscape level is more importantthan fragment size to explain the population patternsof the main tree species. Fragment size was relevant inonly one species, Cordia americana, whereas forestcover resulted relevant in five species. The size-classstructure of Schinopsis balansae, one of the dominantspecies of the upper stratum, appeared to be affected inlandscapes with less forest cover, showing lowerdensities of the smaller classes. Our results show thatfor the conservation of the forest it would be importantto increase their protection degree against the expansionof agriculture, attempting to preserve as much ofthe forest as possible, to promote the forest cover atlandscape level and give relevance even to thesmallest fragments.